Visual methods in psychological research: Developing an open-access set of images for qualitative and reflective work - Brailas, Alexios (Homo Virtualis, 2025)
Implicity is an open-access collection of 55 Creative Commons and public domain images that can be used to facilitate reflective and imaginative engagement in psychological research, education, and related practices. Designed for their projective quality, these images, ranging from abstract compositions and artistic scenes to animals and natural landscapes, invite intuitive, non-verbal responses by activating the brain’s right hemisphere. This collection can support multimodal inquiry methods where participants might select an image that resonates with them and explore its symbolic meaning as a gateway to deeper insight. Such practices help surface unconscious or pre-verbalized aspects of experience, enriching qualitative interviews and reflective exercises. The technique can serve as an opening prompt or a closing ritual, blending intuitive reflection with narrative sense-making. Unlike proprietary card sets, Implicity offers a flexible, open-access alternative that can be used digitally or printed for in-person sessions. Furthermore, recent advances in interpersonal neurobiology clarify why visual methods in psychology are effective: they align with the relational and embodied nature of the mind, activate implicit memory, and support emotion regulation through right-hemisphere engagement. Practitioners are encouraged to adapt the set to their context, adding or removing images as needed. By providing an accessible, ready-to-use resource, Implicity empowers psychologists, educators, and qualitative researchers to integrate imaginative, right-brain processes into their work, enhancing depth, creativity, and participant engagement. The collection is freely available.